Age-specific and gender-dependent impact of primary headache disorders on dementia risk: Population-based longitudinal study - Yin, Jiu-Haw (Medicine (Baltimore), 2018)
Dementia is a global burden of public health. Headache disorders are the third most common cause of disability worldwide and common problems in the elderly population. Few studies focused on the relationship between primary headache disorders (PHDs) and cognitive status, and the results remain controversial. The aim of this countrywide, population-based, retrospective study was to investigate potential association between PHDs and dementia risk. We enrolled 1346 cases with PHDs to match the 5384 individuals by age, gender and co-morbidities. The definition of PHDs, dementia, and risk factors of dementia was identified according to The International Classification of Diseases, Ninth Revision, Clinical Modification. Cox regression was administered for estimating hazard ratios (HR) for dementia. During more than 5 years of follow-up, PHDs individuals had 1.52 times (P <.05) greater risk to develop all dementia compared with individuals without PHDs. Elderly (aged ≥65 years) patients with PHDs displayed significantly higher risk to develop all dementia (P <.01) and non-Alzheimer non-vascular dementia (NAVD) P <.01). Female PHDs individuals were at higher risk of suffering from all dementia (P <.05) and NAVD (P <.05). The influence of PHDs on all dementia was highest in the first 2 years of observation. The results indicated PHDs are linked to a temporarily increased risk for dementia, mainly NAVD, with age-specific and gender-dependent characteristics.